EFEKTIVITAS PELATIHAN MOTIVASI TERHADAP PENINGKATAN PRODUKTIVITAS KARYAWAN BAGIAN EXPECTING PT X - Noviana Rini, Tri; Siwi Widiana, Herlina (Universitas Ahmad Dahlan, 2011)
This research was quasi experimental research aimed at knowing theeffectiveness of motivation training to increase productivity.This researchused non-randomized pretest-posttest control group design. The researchsubjects were 26 employees of Expecting Division (Quality Control) PTX with low productivity. They were randomly divided in two groups,experiment group and control group. Independent Sample T Test wasused to analyze change productivity from gained score. The result showstheres significant difference between experiment group and control groupafter training (t=2.778, p=0.010, p<0.05). The research result shows thatmotivation training is effective to increase productivity.